2020
DOI: 10.3390/ijms21249647
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Metabolomic Analysis of Mothers with a History of Gestational Diabetes Mellitus and Their Offspring

Abstract: Shared metabolomic patterns at delivery have been suggested to underlie the mother-to-child transmission of adverse metabolic health. This study aimed to investigate whether mothers with gestational diabetes mellitus (GDM) and their offspring show similar metabolomic patterns several years postpartum. Targeted metabolomics (including 137 metabolites) was performed in plasma samples obtained during an oral glucose tolerance test from 48 mothers with GDM and their offspring at a cross-sectional study visit 8 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Research into the developmental origins of health and disease ("DOHaD") that occurs in adulthood is inherently challenging because of the difficulty in determining with certainty whether chronic diseases in adulthood are solely related to the intrauterine environment as opposed to all the other potential environmental, cultural, and familial exposures incurred throughout the life course [44][45][46][47]. Despite these obstacles, the possibility of early identification of offspring at risk of future disease remains important, and there are multiple studies showing a linkage between maternal medical conditions during pregnancy and health outcomes in offspring later in life [9][10][11][12][13][47][48][49]. Fetal ultrasound provides a unique opportunity to study the developmental origins of adult-onset disease given that it is immune to the historic confounders that complicate other DOHaD-related investigations, such as sociodemographic factors or other illnesses and exposures throughout childhood and adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research into the developmental origins of health and disease ("DOHaD") that occurs in adulthood is inherently challenging because of the difficulty in determining with certainty whether chronic diseases in adulthood are solely related to the intrauterine environment as opposed to all the other potential environmental, cultural, and familial exposures incurred throughout the life course [44][45][46][47]. Despite these obstacles, the possibility of early identification of offspring at risk of future disease remains important, and there are multiple studies showing a linkage between maternal medical conditions during pregnancy and health outcomes in offspring later in life [9][10][11][12][13][47][48][49]. Fetal ultrasound provides a unique opportunity to study the developmental origins of adult-onset disease given that it is immune to the historic confounders that complicate other DOHaD-related investigations, such as sociodemographic factors or other illnesses and exposures throughout childhood and adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…For offspring, these risks begin in utero but also confer a heightened lifelong risk of diabetes, obesity, and other medical conditions [ 3 9 ]. While family history of T2D is a known risk factor for developing diabetes, there is emerging evidence that suggests a worsening disease severity with each successive generation affected [ 10 12 ]. Additionally, T2D is associated long-term with chronic renal disease including the need for dialysis or transplant [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intergenerationally correlated metabolites included carnitine (C0), glycerophospholipid (PC ae C34:3), two biogenic amines (taurine, creatinine), an amino acid (proline), and sphingolipid (SM-(OH) C14:1). The authors suggested a possible long-term programming effect of maternal GDM on metabolic health in children [ 115 ]. Conversely, even though Shokry et al also found altered metabolites in the cord blood, associated with anthropometric changes in newborn children of mothers with GDM and obesity, these alterations were not detected longitudinally.…”
Section: Metabolomic Changes In Offspring After Exposure To Maternal Diabetesmentioning
confidence: 99%
“…[ 16 ]. Plasma metabolomics provides information about individual biological status arising from genetic and environmental interaction [ 17 ]. Previous studies have shown the correlation between various metabolites and incidences of metabolic disorders such as impaired glucose tolerance and insulin resistance [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%